An evaluative study of teacher preparation program at the faculty of education, Sultan Qaboos university, based on the requirements of academic accreditation - Belqees Qaleb Al-Shar'ai (University of Science and Technology, Yemen, 2008)
Abstract                                                                                                   The faculty of education at Sultan  Qaboos Univeristy started in 2004 developing the quality of its academic programs as well as its technical and administrative services international academic accreditation programs. Accordingly, the faculty sought to prepare self-evaluation report as a main requirement for accreditation, as it believes with its significant  future role in for teacher preparation in order to be able to practice teaching based on society needs and time requirements. The study aimed to identify strengths and weaknesses in the program based on the requirements of academic accreditation standards for teacher preparation program through the following questions: • What are the opinions of the graduates of the faculty of education on the teacher preparation program based on the requirements of academic accreditation standards? • Is there any statistically significant difference in the point of view of the graduates of the faculty regarding the teacher preparation program based on the requirements of academic accreditation standards that can be attributed to any of the study variables: gender, specialty, or participation in students unions? • What are the strengths and weaknesses in teacher preparation program of the faculty of education at Sultan Qaboos University from the point of view of its graduates? The results reveal differences in the graduates opinions that ranges from high to average, which gives good indications generally, and they were above average regarding what graduates learnt from the program. This assures that the program is on track to its final goal to development based on requirements of academic accreditation standards so as to gain accreditation and enabling the faculty from realizing its mission in the best way possible.